If (1 – p) is a root of quadratic equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\] , then both the roots are:-
a)0, -1
b)-1, 1
c)0, 1
d)-1, 2
Answer
Verified
463.5k+ views
Hint: Every quadratic equation is of the form
\[\begin{align}
& a{{x}^{2}}+bx+c=0 \\
& which\ on\ conversion,\ we\ get \\
& {{x}^{2}}-\left( \dfrac{-b}{a} \right)x+\dfrac{c}{a}=0 \\
\end{align}\]
The coefficient of x gives the sum of the roots of the given equation with an appropriate negative sign that is \[\left( \dfrac{-b}{a} \right)\]. The constant term of the equation will give the product of the two roots of the equation \[\dfrac{c}{a}\] . Now, using these properties, one could get to the solution.
Complete step by step answer:
Every quadratic equation is in the form, ${{x}^{2}}-Sx+P=0$(where ‘S’ is the sum of the roots and ‘P’ is the product the roots).
We are given that one of the roots of the given equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]is (1-p). Let $\alpha $be the other root of the equation.
Sum of the roots$=-p.....................(1)$
Product of the roots=$(1-p)......................(2)$
On comparing the equation given in the question with the general equation, we get,
Sum of the roots ,$S=(1-p)+\alpha ................(3)$
Product of the roots ,$P=(1-p)\alpha ...................(4)$
Equating (1) and (3), we get,
$-p=1-p+\alpha $
$\therefore \alpha =-1$
Hence, one of the roots of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\] is -1.
Substituting for $\alpha $ in (4) and equating it with (2), we obtain,
$1-p=-(1-p)$
$2=2p$
$\therefore p=1$
We know that, (1-p) is a root of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\],
$\therefore 1-p=1-1=0$
Hence, one of the roots of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]is 0.
$\therefore $ The roots of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]are 0 and -1.
So, the correct answer is “Option a”.
Note: Alternate method:
We have,
\[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0......................(1)\]
We are given (1 – p) is a root of quadratic equation\[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\] .
Hence, on substituting $x$ by (1 – p), we get,
\[{{(1-p)}^{2}}+\text{ }p(1-p)\text{ }+\text{ }\left( 1\text{ }\text{ }p \right)\text{ }=\text{ }0\]
Taking (1-p) common for all the terms, we obtain,
\[(1-p)\left( (1-p)+p+1 \right)=0\]
\[(1-p)\left( 2 \right)=0\]
Since, 2 is a constant and cannot take the value of zero,
\[1-p=0\]
\[\therefore p=1\]
Substituting p=1 in equation (1), we obtain,
\[{{x}^{2}}+\text{ (1)}x\text{ }+\text{ }\left( 1\text{ }\text{ 1} \right)=0\]
\[{{x}^{2}}+\text{ }x\text{ }=0\]
$x(x+1)=0$
Hence,
$x=0.............(2)$
$x+1=0$
$x=-1...............(3)$
$\therefore $ From (2) and (3), the zeroes of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]are 0 and -1.
\[\begin{align}
& a{{x}^{2}}+bx+c=0 \\
& which\ on\ conversion,\ we\ get \\
& {{x}^{2}}-\left( \dfrac{-b}{a} \right)x+\dfrac{c}{a}=0 \\
\end{align}\]
The coefficient of x gives the sum of the roots of the given equation with an appropriate negative sign that is \[\left( \dfrac{-b}{a} \right)\]. The constant term of the equation will give the product of the two roots of the equation \[\dfrac{c}{a}\] . Now, using these properties, one could get to the solution.
Complete step by step answer:
Every quadratic equation is in the form, ${{x}^{2}}-Sx+P=0$(where ‘S’ is the sum of the roots and ‘P’ is the product the roots).
We are given that one of the roots of the given equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]is (1-p). Let $\alpha $be the other root of the equation.
Sum of the roots$=-p.....................(1)$
Product of the roots=$(1-p)......................(2)$
On comparing the equation given in the question with the general equation, we get,
Sum of the roots ,$S=(1-p)+\alpha ................(3)$
Product of the roots ,$P=(1-p)\alpha ...................(4)$
Equating (1) and (3), we get,
$-p=1-p+\alpha $
$\therefore \alpha =-1$
Hence, one of the roots of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\] is -1.
Substituting for $\alpha $ in (4) and equating it with (2), we obtain,
$1-p=-(1-p)$
$2=2p$
$\therefore p=1$
We know that, (1-p) is a root of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\],
$\therefore 1-p=1-1=0$
Hence, one of the roots of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]is 0.
$\therefore $ The roots of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]are 0 and -1.
So, the correct answer is “Option a”.
Note: Alternate method:
We have,
\[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0......................(1)\]
We are given (1 – p) is a root of quadratic equation\[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\] .
Hence, on substituting $x$ by (1 – p), we get,
\[{{(1-p)}^{2}}+\text{ }p(1-p)\text{ }+\text{ }\left( 1\text{ }\text{ }p \right)\text{ }=\text{ }0\]
Taking (1-p) common for all the terms, we obtain,
\[(1-p)\left( (1-p)+p+1 \right)=0\]
\[(1-p)\left( 2 \right)=0\]
Since, 2 is a constant and cannot take the value of zero,
\[1-p=0\]
\[\therefore p=1\]
Substituting p=1 in equation (1), we obtain,
\[{{x}^{2}}+\text{ (1)}x\text{ }+\text{ }\left( 1\text{ }\text{ 1} \right)=0\]
\[{{x}^{2}}+\text{ }x\text{ }=0\]
$x(x+1)=0$
Hence,
$x=0.............(2)$
$x+1=0$
$x=-1...............(3)$
$\therefore $ From (2) and (3), the zeroes of the equation \[{{x}^{2}}+\text{ }px\text{ }+\text{ }\left( 1\text{ }\text{- }p \right)\text{ }=\text{ }0\]are 0 and -1.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE